PELUANG PEMANFAATAN TEKNOLOGI BIG DATA PADA UMKM DI INDONESIA UNTUK MENINGKATKAN KINERJA PERDAGANGAN DI ERA INDUSTRI 4.0 - Bunga Amira; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
Utilization of Big Data Technology is a significant opportunity to improve the trade performance of Micro, Small and Medium Enterprises (MSMEs) in Indonesia in the Industry 4.0 era. through qualitative literature studies. The findings show that leveraging Big Data technology can provide significant benefits for MSMEs, including better understanding of markets and customers, personalization of customer experiences, more efficient inventory management, more informed decision making, and product and service innovation. However, the challenges faced by MSMEs in adopting Big Data technology include limited resources, limited expertise, data security issues, and cultural barriers.